Analysis Of Payment Accounting System At Pt Aplus Pasific - Ertie Nur Hartiwati (Publisher Cv. Inara, 2021)
To find out whether a company is a company that has a good and correct system, a control system is needed that can make the company more thorough and have more specific and good payroll data. The internal control system is one of the accounting information systems. implemented by the company in achieving its corporate goals. In realizing a good and appropriate company system, an analysis and evaluation is needed. Where it is expected to be able to prevent fraud that can occur within a company. The analytical method used is Flowchart (Flow Chart), an analytical technique used to describe several aspects of an information system in a clear, concise, and logical manner. Flowcharts use standard symbols to describe through pictures the transaction processing procedures used by the company and the flow of data through the system. The benefits of this system to help clarify complex processes in the decision-making process. The conclusions obtained from the Payroll Accounting Information System Analysis, the company seeks to implement the accounting function properly. However, the company has not implemented a payroll information system that is more complex so that it can cause errors in the payroll system within the company.